Pressão e tecnologia na infância: o brincar e se-movimentar e a incessante forma de expressão em um mundo acelerado - Tolfo, Jéssica Comoretto (2019)
This study aims to investigate the pressures that children are being put currently, highlighting influences of adults in rushing the child to become prepared for the future, ie, placed early in extracurricular activities, always aiming at "learning", also highlighting the interventions of technologies in the child's daily life and the consequences of their excessive use, the problem, then, is how to understand the child in an accelerated world, in which the pressure of current times and technology has influenced the child's play? Thus this research is characterized as a theoretical research, because it aims at an evolution of the theme seeking to deepen this debate. Thus, this research has as a general objective to understand how the pressure of the current times, together with the excessive use of technologies has been influencing the child's free play and self-movement. With this discussions on understanding to understand the child, as well as, criticism presented about the pressures in which children are currently placed were developed. As a result of this, the reflections on children's lives are noted, such as: spoiled, monitored and connected children, early schooling and the consequences that the excessive use of technologies can bring. Moreover, play for the child is its form of expression and learning, while for the adult it is seen as a "springboard" to the future. Thus, bringing the Play and Be-Movement with the main form of expression of the child. The intention is not to extenuate with the subject, but to call the attention of parents, family members, teachers, in short, adults on the importance that free play and self-movement provides for the child, consisting of existential and vital for the child.